Analisis Kepuasan Pelanggan Dengan Menggunakan Metode Importance Performanced Analysis Dapoer Nides. - Madeali, Wahyu; Nurmutia, Syahreen; Jauhari, Junaenah; Feblidiyanti , Niera (Program Studi Teknik Industri Universitas Teknologi Sumbawa, 2025)
The COVID-19 pandemic has changed the landscape of the culinary industry. Changes in consumer behavior that tend to cook and eat at home due to stay at home and social distancing policies have triggered a shift in consumption patterns from offline to online, with e-commerce becoming the new backbone. Product availability, functionality, and speed and convenience of delivery are the main driving factors for consumer shopping decisions. In this context, service quality plays a crucial role in creating customer satisfaction. This study focuses on five dimensions of service quality determinants, Reliability, Responsiveness, Assurance, Empathy, and Tangible, to understand and strengthen service strategies amidst the dynamics of the post-pandemic culinary industry. The purpose of the study is to determine what factors are the weaknesses in the quality of restaurant service, and how to increase restaurant sales. The Importance and Performance Analysis (IPA) analysis shows priority areas for service improvement to increase customer satisfaction: Tangibles, namely the need for improvements to conditions and chairs. Reliability: Improving services according to promises and ease of payment. Maintain the speed of delivery and taste of the food.. Responsiveness is Improving the speed of employee service and their ability to answer questions. Maintaining the ease of order delivery. Assurance is improving the consistency of good service to all customers. Maintain parking security. and Empathy is Maintaining opening hours according to promotions.